The interpretive power of setting: appropriate levels of restoration and development at Copán Archaeological Park, Honduras; a UNESCO World Heritage Site - Mayer, Christopher C., author; Wallace, George N., advisor; Loomis, Ross J., committee member; Merriman, Tim F., committee member; Vaske, Jerry J., committee member (Colorado State University. Libraries, 2007)
Copán Archaeological Park (CAP) is a small but world-renowned cultural site facing important management decisions that will affect both internal and external setting attributes, interpretive potential, and the ruins experience. Managers must choose an appropriate level of restoration internally and work with local officials to achieve appropriate land uses adjacent to the park. In 2002 and 2003, visitor perceptions about these issues were probed using 700 plus post-visit surveys and two sets of on-site interviews. This study examined how differing levels of restoration and development within, and intensifying development next to CAP would affect interpretive potential and the visitor experience. Results indicated that Latin Americans, North Americans, and Europeans all preferred a mixture of restored ruins and those being reclaimed by nature. Visitors describe how this juxtaposition added to their experience. A majority of these visitors indicated a strong preference for maintaining agricultural or forested lands between the park and the town of Copán Ruinas and described how the intensification of development would deleteriously affect their experience. Protecting interpretive potential inherent in these settings will require interpreters to move beyond traditional interpretive planning and to inform the protected area and local government planning decisions that will ultimately determine the "from which" that programmatic interpretation is derived. Implications for Park management and cross-boundary involvement in land use decisions at this and similar site are discussed and recommendations given. If CAP and adjacent lands are managed properly, CAP can provide visitors with a unique experience that will maintain or broaden the site's appeal. The dissertation contains two stand-alone papers. Chapter IV examines appropriate levels of restoration and development and the setting attributes affecting the visitor experience. Chapter V identifies and provides suggestions for protecting the interpretive potential of the internal and external setting at CAP.
Keywords: recreation